Market Entry into the USA Why European Companies Fail and How to Succeed - Drews, Ralf; Lamson, Melissa (Management for Professionals,, 2016)
This book connects a buying psychology driven by American beliefs and values with a company's go-to market strategy, the goal being to sensitize readers to how the cultural values of a particular country or region can impact the business environment. The book also addresses the reasons behind these differences and therefore begins with a detailed cultural comparison of the United States and Europe, and assessments of how these characteristics impact their respective markets and customer behavior differently. Another aspect that sets this book apart is that it argues for sound decision-making processes as the first priority in any international business strategy. Readers are provided detailed insights into the variables a European company needs to understand before it makes its "go/no-go" decision, along with the tools needed to evaluate the probability of success and the risks of going to market. Once a company decides to enter the US market, the book then offers a highly customer-centric approach to developing and executing an effective market strategy.